Emerging concepts in the diagnosis, treatment, and prevention of travelers' diarrhea. Issue 5 (October 2019) - Schweitzer, Lorne; Singh, Bhagteshwar; Rupali, Priscilla; Libman, Michael
Abstract : Purpose of review: Traveller's diarrhea, though not life-threatening. is often a vexing problem, which impacts overall function of the traveller while on holiday. Increasing data is available regarding molecular diagnostic techniques, which may help obtain an early etiologic diagnosis. Use of antibiotics for traveller's diarrhea is controversial in this era of multidrug resistance and microbiome disruption. Recent findings: Travel to the tropics promotes gut colonization with drug-resistant bacteria and this risk increases after treatment with antibiotics, leading to potential ecological impacts in the country of residence. Summary: Traveller's diarrhea is common and can impact a traveller's itinerary leading to significant inconvenience, and occasional longer term sequelae. Though bacterial causes predominate, recommended treatment is conservative in mild-to-moderate cases. Molecular techniques for early diagnosis of traveller's diarrhea may help with appropriate management. Treatment with antibiotics is sometimes required but is associated with gut colonization by multidrug-resistant bacteria.